Study of the Effect of Leavening Agent and the Addition of Fish in the Making of Sweet Potato Fish Crackers - Muhammad Panji G. Setiawan; Herla Rusmarilin; Sentosa Ginting (Universitas Sumatera Utara, 2013)
The aim of this research was to determine the effect of the amount of pora-pora fish and leavening agent concentration on the chemico-physical and organoleptic properties of sweet potato fish crackers. This study used a completely randomized design (CRD) with two factors: the amount addition of fish, i.e., 10%, 20%, 30% and 40% and baking powder concentration, i.e., 0.1%, 0.2 %, 0.3% and 0.4%. Observed parameters were moisture content, ash content, protein content, fiber content and organoleptic tests (color, aroma, flavor, and texture).The results showed that the addition of pora-pora fish had highly significant effect on moisture content, ash content, protein content, fiber content and organoleptic tests (color, aroma, flavor, and texture). The Leavening agent concentration had highly significant effect on moisture content, ash content, protein content, fiber content and organoleptic tests (color, flavor, and texture) and had significant efffect on aroma. Interaction of the amount of pora-pora fish and leavening agent concentration had highly significant effect on moisture content, protein content and fiber content, and had significant effect on ash content, aroma and texture, and had no significant effect on color and flavor. Twenty percent of pora-pora fish and 0.2% of leavening agent gave the best crackers. Key words : Crackers, pora-pora fish, sweet potato, leavening agent